G Gambaran Integritas Diri Pada Lansia Di Panti Wredha - Budi Cahyanti, Retno; Sartika Sari, Febriana; Syolihan Rinjani Putri, Diyanah (Jurnal Kesehatan, 2020)
Abstract The number of the elderly in Indonesia increases adequately significantly (Putri, 2019). Life expectancy in Indonesia reaches 71 years old. Based on the population projection of the National Board of Statistics in 2019, as of 2010 the number of elderly population has increased, indicating that there is a transition towards an ageing population. In 2019, the number of the elderly population was 9.7% out of the total number of population or equalled to approximately 25.9 million people. In 2035, the number of elderly population will approximately reach 48 million people (15.77%), or will nearly triple that of the elderly population in 2010. The objective of this research is to investigate overview of self-integrity of the elderly at Dharma Bhakti Nursing Home of Surakarta. This research used the quantitative descriptive analytical research method with cross sectional approach. Its population was all of the elderly as many as 66 persons cared at Dharma Bhakti Nursing Home of Surakarta. Total sampling was used to determine its samples. The data of the research were analyzed by using the Deskriptif analysis. The result of the frequency analysis shows that the lowest score of the self-integrity was 5, and the highest one was 24 with the average score of 17.45 and the standard deviation of 3.259. Thus, the average score of self-integrity of the elderly was 17.45. Abstrak Jumlah penduduk lansia di Indonesia mengalami peningkatan yang cukup signifikan (Putri, 2019). Usia Harapan Hidup di Indonesia mencapai 71 tahun. Berdasarkan hasil proyeksi penduduk Badan Pusat Statistik tahun 2019, jumlah penduduk lansia terjadinya peningkatan mulai dari tahun 2010 yang menunjukkan adanya transisi menuju struktur penduduk tua (ageing population). Pada tahun 2019, jumlah penduduk lansia sebesar 9,7% dari total jumlah penduduk atau sekitar 25,9 juta orang. Tahun 2035 diperkirakan sebesar 48 juta (15,77%), atau hampir tiga kali lipat dibanding pada tahun 2010. Penelitian ini bertujuan untuk mengetahui gambaran integritas diri pada lansia di Panti Wredha Dharma Bhakti Surakarta. Jenis penelitian yang digunakan adalah penelitian kuantitatif, menggunakan rancangan penelitian deskriptif analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah Semua lansia yang dirawat di Panti Wredha Dharma Bhakti Surakarta yang berjumlah 66 orang. Pengambilan sampel dalam penelitian ini menggunakan total sampling. Analisa data dalam penelitian ini menggunakan uji Analisis Deskriptif. Hasil penelitian menunjukkan Hasil analisis frequency menunjukkan bahwa integritas diri apda lansia memiliki nilai terendah 5, tertinggi 24 dengan rata-rata 17,45 dan standar deviasi 3,259. Kesimpulan pada penelitian ini menunjukkan bahwa rata-rata integritas diri pada lansia adalah 17,45.